PSEUDOTUMOR FOLLOWING METALONPOLYETHYLENE TOTAL HIP ARTHROPLASTY A REPORT OF THREE CASES - Damjanovikj, Dejan; Kamnar, Viktor; Atanasov, Nenad; Samardjiski, Milan; Georgieva, Daniela; Komnenovikj, Marina; Atanasovski, Igor; Asani, Durim; Zlateska, Aleksandra (Македонска асоцијација на ортопеди и трауматолози = Macedonian Association of Orthopedics and Traumatology, 2022)
Introduction: One of the rare complications of the total hip arthroplasty are pseudotumors. They are defined as granulomatous or destructive cystic lesions with nonneoplastic and noninfective origin. Typically there is latent period of 2 to 15 years from the implantation of the endoprosthesis to the clinical manifestation of the lesion. Most common symptoms are pain, swelling and discomfort but also, loosening of the components of the endoprosthesis or compressive symptomatology can occur. Potential mechanisms of development of psudotumors are foreignbody reaction, hypersensitivity reaction and excessive wear debris reaction. Case reports: We report three cases of pseudotumors following metalonpolyethylene total hip arthroplasty. The first case is 76yearold women presented with pain and limited motion of the right hip, 18 years after the hip arthroplasty. The second case is 53yearold man presented with pain and swelling in the right trochanteric region, 21 years after the hip arthroplasty. The third case is 55yearold women presented with painless, large mass in the left proximal thigh, 13 years after the hip arthroplasty. All three patients were treated operatively with extirpation of the pseudotumor. Discussion: Patients with hip or groin pain, a mass, or a fluid collection following total hip arthroplasty should be carefully evaluated, especially for the presence of infection. Unfamiliarity with pseudotumors may lead clinicians and radiologists to misinterpret these masses as worrisome for malignancy. The management of pseudotumors is controversial since there is no clear consensus for optimal treatment or surveillance. Conclusion: The recognition of pseudotumor is very important considering the increasing number of surgical procedures and consequential postoperative complications. Pseudotumors are a rare but important complication occurring in hip replacement surgery using all different types of implants.
Keywords: pseudotumor; total hip arthroplasty; metalonpolyethylene